2008
DOI: 10.1348/147608307x252393
|View full text |Cite
|
Sign up to set email alerts
|

No strong evidence for abnormal levels of dysfunctional attitudes, automatic thoughts, and emotional information‐processing biases in remitted bipolar I affective disorder

Abstract: It appears that individuals with remitted bipolar affective disorder do not show cognitive vulnerability as proposed in Beck's theory of depression if they only report subthreshold levels of depressive symptoms. Perhaps, the cognitive vulnerability might only be observable if mood induction procedures are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
2
36
1
Order By: Relevance
“…The lack of difference in the current study is consistent with the findings from published studies that the DAS and its subscales rarely distinguish between bipolar and unipolar groups (e.g. Jones et al 2005;Lex et al 2008). Indeed, Silverman et al (1984) found that the remitted bipolar scored lower on the DAS than clinical controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of difference in the current study is consistent with the findings from published studies that the DAS and its subscales rarely distinguish between bipolar and unipolar groups (e.g. Jones et al 2005;Lex et al 2008). Indeed, Silverman et al (1984) found that the remitted bipolar scored lower on the DAS than clinical controls.…”
Section: Discussionsupporting
confidence: 92%
“…However, three published studies have not found elevated scores on the DAS in bipolar disorder compared to non-clinical controls, despite adequate methodological designs (Alatiq et al in press;Lex et al 2008;Silverman et al 1984). Indeed Silverman et al (1984) found lower levels of dysfunctional attitudes in a bipolar group compared to unipolar depression and non-clinical controls.…”
Section: Introductionmentioning
confidence: 97%
“…However, these au thors demonstrated additionally that the performance of BD patients may depend on the emotional intensity of the processed stimuli, being substantially improved on the presence of the stimuli extremely negative, but not moderately negative. This hypothesis is particularly in teresting as it indicates the possible reasons of nonexist ence of the differences between BD patients and healthy controls in the emotional memory tasks conducted by other authors (Derntl et al, 2009;Lex et al, 2008). It is also important to highlight that, according to Kau erSant'Anna et al (2008) and Malhi et al (2005), BD euthymic patients perceive the stimuli with negative va lence in an altered way, rating them as more negative than healthy controls.…”
Section: Discussionmentioning
confidence: 80%
“…This bias can be also observable in bipolar remitted patients subjected to high or low mood induction (Nutt & Lam 2011). On the other hand, in the absence of clinically significant symptoms and in the presence of stabilized mood, the retrieval of emotional information seems to be not affected by its valence (Derntl, Seidel, KryspinEx ner, Hasmann, & Dobmeier, 2009;Lex, Meyer, Marquart, & Thau, 2008). Additionally, in a memory task involving positive and negative stimuli bipolar euthymic patients tend to respond in a way comparable to that of healthy adults (Derntl et al, 2009;Lex et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation